2017
DOI: 10.1371/journal.pone.0182291
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibition prevents cell death induced by loss of tricellular tight junction proteins in temperature-sensitive mouse cochlear cells

Abstract: Tricellular tight junctions (tTJs) are specialized structures that occur where the corners of three cells meet to seal adjacent intercellular space. The molecular components of tTJs include tricellulin (TRIC) and lipolysis-stimulated lipoprotein receptor (LSR) which recruits TRIC, are required for normal hearing. Although loss of TRIC causes hearing loss with degeneration of cochlear cells, the detailed mechanisms remains unclear. In the present study, by using temperature-sensitive mouse cochlear cells, US/VO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…18 Another study using the temperature-sensitive mouse cochlear cells (US/VOT-E36 cell line) showed that metformin enhanced the expression of tricellulin and lipolysis-stimulated lipoprotein receptor (proteins required for normal hearing) during cell differentiation via 5′-adenosine monophosphate-activated protein kinase. 19 Animal studies also support the potential benefit of metformin in preventing hearing loss. [20][21][22][23][24][25][26] In humans, 1 previous observational study conducted in Taiwan by Chen et al 27 showed a beneficial effect of metformin on the risk of sudden deafness.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…18 Another study using the temperature-sensitive mouse cochlear cells (US/VOT-E36 cell line) showed that metformin enhanced the expression of tricellulin and lipolysis-stimulated lipoprotein receptor (proteins required for normal hearing) during cell differentiation via 5′-adenosine monophosphate-activated protein kinase. 19 Animal studies also support the potential benefit of metformin in preventing hearing loss. [20][21][22][23][24][25][26] In humans, 1 previous observational study conducted in Taiwan by Chen et al 27 showed a beneficial effect of metformin on the risk of sudden deafness.…”
mentioning
confidence: 88%
“…Cellular studies suggested that metformin, via limiting the production of reactive oxygen species, might attenuate the toxic effects in auditory cell lines (HEI‐OC1 cells) treated with gentamicin 17 and cisplatin 18 . Another study using the temperature‐sensitive mouse cochlear cells (US/VOT‐E36 cell line) showed that metformin enhanced the expression of tricellulin and lipolysis‐stimulated lipoprotein receptor (proteins required for normal hearing) during cell differentiation via 5′‐adenosine monophosphate‐activated protein kinase 19 . Animal studies also support the potential benefit of metformin in preventing hearing loss 20‐26 …”
mentioning
confidence: 99%
“…1). 28 The cells were cultured in minimum essential medium (Nacalai Tesque, Inc., Kyoto, Japan) supplemented with 10% fetal bovine serum (FBS; Invitrogen, Carlsbad, CA), 100 µg/ml streptomycin, and 50 µg/ml amphotericin B. The cells were plated on 60-mm culture dishes (Corning Glass Works, Corning, NY) coated with rat-tail collagen (500 µg dried tendon/ml in 0.1% acetic acid) and incubated in a humidified atmosphere with 5% CO 2 at 33C.…”
Section: Methodsmentioning
confidence: 99%